Karakterisasi Tanah Salin di Wilayah Pesisir Kecamatan Banda Mulia Kabupaten Aceh Tamiang - Nurlia Nurlia; Zainabun Zainabun; Darusman Darusman (Jurnal Ilmiah Mahasiswa Pertanian, 2020)
Abstract. Coastal land located in the District of Kota Mulia directly adjacent to the sea is thought to have suffered salinization due to the tide. Indicated by the presence of water sources (such as wells, and wells drilled) were salted and morphological disruption of plants that grow in the region. The purpose of this study was to determine the morphological characteristics, physical and chemical soil saline and memetakanya with quantitative descriptive method based on field observations and laboratory analyzes. Salinity measurement results based on the value of electrical conductivity (EC) of land in this area has five criteria, namely non copy, the copy is very low, slightly saline and highly saline. Land categorized the copy is a criterion rather copy, copy and highly saline, with a base element that dominates is Na and Mg. Saline soils in this region has a highly acidic pH, SAR values of tranquility and saturation Na generally 15%.Characterization of Salin in the Coastal Region of Banda Mulia District, Aceh Tamiang RegencyAbstract. The coastal land located in the Banda Mulia Subdistrict which is directly adjacent to the sea is thought to have undergone salinization due to tides. Indicated by the presence of salty water sources (such as wells and drilled wells) and the morphological disturbance of plants growing in the region. The purpose of this study was to determine the morphological, physical and chemical characteristics of saline soil and map it with quantitative descriptive methods based on field observations and laboratory analysis. Salinity measurement results based on the value of Electrical Conductivity (EC) of lands in this region have five criteria, namely non-saline, very low saline, near saline and very saline. Saline is categorized as a rather saline, saline and very saline, with the basic elements dominating are Na and Mg. Saline soils in this region have very acidic pH, low SAR value and Na saturation in general 15%.